2020
DOI: 10.1002/anie.202002560
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Electron Reactions Enabled by Anion‐Based Redox Chemistry for High‐Energy Multivalent Rechargeable Batteries

Abstract: The development of multivalent metal (such as Mg and Ca) based battery systems is hindered by lack of suitable cathode chemistry that shows reversible multi‐electron redox reactions. Cationic redox centres in the classical cathodes can only afford stepwise single‐electron transfer, which are not ideal for multivalent‐ion storage. The charge imbalance during multivalent ion insertion might lead to an additional kinetic barrier for ion mobility. Therefore, multivalent battery cathodes only exhibit slope‐like vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 40 publications
2
115
1
Order By: Relevance
“…[16] Recently,Saha et al presented fundamental research on the bottlenecks of Sr edox, [17] in which an ew material Li 1.33À2y/3 Ti 0.67Ày/3 Fe y S 2 (y = 0.3) was capable of ar eversible capacity as high as 245 mAh g À1 .T he high capacity resulted from the existence of 3d 6 electrons in the Fe 2+/3+ redox couple that activated the anionic Sr edox. During the final review stage of this manuscript, See et al revealed the electrochemistry of aL i-rich layered iron sulfide Li 2 FeS 2 , [18] whereas Zhao-Karger reported on multivalent cation storage in VS 4 , [19] further emphasizing the rising importance of this class of materials.…”
Section: Introductionmentioning
confidence: 99%
“…[16] Recently,Saha et al presented fundamental research on the bottlenecks of Sr edox, [17] in which an ew material Li 1.33À2y/3 Ti 0.67Ày/3 Fe y S 2 (y = 0.3) was capable of ar eversible capacity as high as 245 mAh g À1 .T he high capacity resulted from the existence of 3d 6 electrons in the Fe 2+/3+ redox couple that activated the anionic Sr edox. During the final review stage of this manuscript, See et al revealed the electrochemistry of aL i-rich layered iron sulfide Li 2 FeS 2 , [18] whereas Zhao-Karger reported on multivalent cation storage in VS 4 , [19] further emphasizing the rising importance of this class of materials.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, this anion-based redox chemistry (anionic redox) has recently drawn quite some attention with respect to the increase in the energy density of Li-, Na-and Mg-ion batteries, see, e.g., Refs. 62,63 To elucidate this anionic redox, we performed a Bader charge analysis 64 and calculated charge density differences 65 for MgSc 2 S 4 . Details of this charge analysis can be found in the Supplementary Information.…”
Section: Resultsmentioning
confidence: 99%
“…Although a significant drop in reversible capacity was observed when the temperature was lowered (≈80 mAh g −1 at room temperature vs 170 mAh g −1 at 60 °C), it is still far better than micrometer-sized TiS 2 , which exhibited extremely poor electrochemical performance at room temperature. These results showed that obtaining a reversible reaction of Mg cathode is far difficult compared to that of Li cathode and hence nanosizing of cathode materials [12,27,29,31,36,39,42,43,[45][46][47][48]50,68,70,[86][87][88]90,[92][93][94][95][96][97][98].…”
Section: Tmdsmentioning
confidence: 99%